The Implementation Sea Toll and Supply Chain in Indonesia Development as Maritime Country - Fausta Ari Barata (Jurnal Mantik, 2021)
The logistic system, national supply chain effective has performance as a key factor from economic development sustainable, and will push Indonesia able to seize them sea, and made Indonesia a maritime axis in the world. In other that the purpose of this research is to explain the problems which cause the program sea toll program is not optimal, and how is the solution of settlement in other that sea toll can synergy with supply chain and national logistic, to become a strong maritime, the result of the research is the minimum human resources problem which has tricked with multiply education institution and logistic sector training and water transportation. For water transportation is still in the center of the high economy activities area, the government has made concept ship promote the trade. The development of connectivity in the east area of Indonesia expected to increase the activity of the economy and trading. If infrastructure in the east Indonesia area, the society, businessman, and water transportation user will think hard to take infrastructure to be batter economic rotation. The government issue, government regulation number 70 of 2017 about organizing obligation of public service to transport from and to underdeveloped regions, isolated, contracting, and the border of government to improve all sea infrastructure and rejuvenate on all infrastructure of sea toll. Then the government cut regulation overlap and give easy to businessman ship procurement, in away borrow to a bank which makes a ship as mortgages.